Management of enterprise logistics activities - Zhou, Peng (Харківський національний автомобільно-дорожній університет, 2024)
The qualification work defines the essence of the concepts "logistics," "logistics system," and "enterprise logistics activities," as well as their characteristics, components, functions, and tasks. It examines the functions, principles, and approaches to managing logistics activities at the enterprise level and analyzes the operational results of PJSC "RTE - 16355" over the past five years. A methodological approach to assessing the efficiency of managing logistics activities was improved and tested. Measures to enhance logistics management were proposed, specifically the reengineering of the "transportation" business process. A techno-economic assessment of the practical recommendations was conducted. Future research prospects include studying individual logistics business processes within the enterprise to identify reserves for improving their efficiency.
Keywords: logistics activities of the enterprise; logistics system; logistics business processes; and management efficiency assessment